THE EFFECTS OF ELECTROMAGNETIC RADIATIONS FROM CONVENTIONAL AND ADVANCED MOBILE PHONE ON THE HISTOMORPHOLOGY OF PROXIMAL TUBULES OF MESONEPHROS OF CHICK EMBRYO: Effects of Electromagnetic Radiations - ., Dr Sabah Rehman; Butt, Shadab Ahmed (Pakistan Armed Forces Medical Journal, 2013)
Objective: The study was conducted to investigate the comparative histomorphogical effects of radiations from conventional and advanced mobile phone, on the developing kidney of the chick embryo. Study Design: Randomized control trial. Duration of Study: Three months. Material and Methods: Fifty fertilized eggs of Fayoumibreed were selected. Two groups II and IV were exposed to conventional mobile phone radiation and two groups III and V was exposed to advanced mobile phone radiation for 15 and 30 minutes respectively, group I, being the control. Results: The results were significant between control and groups III, IV and V regarding tubular diameter. The luminal diameters were statistically insignificant between the respective groups but significant between groups I and all the experimental groups, II and III when comparing proximal tubular cell’s height. Conclusion: The proximal tubular and luminal diameters and epithelial height of the cells lining the proximal tubules of mesonephros were affected by not only advancement in the mobile phones but also increase in the exposure time to the radiations.